Young ethnic German late resettlers from Poland –“(quasi)-forced nature of migration” vs. success of integration - Tomaszewska, Magdalena (Journal of Education Culture and Society, 2020)
“(Late) resettlers”, or to put it in simple terms, people of German ancestry who came to Germany from Eastern Europe after World War II, constitute a peculiar case within the spectrum of German migration. On one hand, they are distinct from foreigners, on the other hand, despite having German citizenship, they stand out from the native German population.L. Wilkiewicz refers to this category as “quasi-forced resettlers”. The forced nature of the young resettlers migration may then be seen as doubly strengthened by the fact that they had no impact on their parents decision to leave the country. They were, in a sort of way, uprooted from their original environment and planted into a new, alien one. Having accepted German citizenship and having been attributed the purpose of “living as Germans among Germans”, the resettlers were expected to show a higher degree of integration with local society than “ordinary” migrants. In this study, I shall confine myself to a few selected aspects affecting the success of integration. Presented below are some of the memories that the young resettlers have of the moment of their “(quasi)-forced” migration, of their early days in Germany, of Poland as the country of their childhood, of the reasons for departure as given by their parents, and of the main factors – apart from those personality-related such as intelligence –that contributed to their successful integration.